Beneficiary effect of nanosizing ferric pyrophosphate as food fortificant in iron deficiency anemia: evaluation of bioavailability, toxicity and plasma biomarker1. Issue 76 (19th August 2015) - Srinivasu, Bindu Y.; Mitra, Gopa; Muralidharan, Monita; Srivastava, Deepsikha; Pinto, Jennifer; Thankachan, Prashanth; Suresh, Sudha; Shet, Arun; Rao, Suguna; Ravikumar, Gayatri; Thomas, Tinku S.; Kurpad, Anura V.; et al.
<x xml:space="preserve">Abstract</x> NP-Fe4(P2O7)3 significantly improved hemoglobin level in iron-deficient rats and Fetuin-B showed differential biological response across NP doses through plasma proteomics.